Investigation of Paleolithic Localities in the Faid Area of Ha’il in Northwest Saudi Arabia - Nassr, Ahmed; Elhassan, Ahmed; al-Hajj, Mohammed; Tueaiman, Ali; Alshudukhi, Naif (Jordan Journal for History and Archaeology, 2023)
The ongoing archaeological survey and excavations in the Faid area in northwest Saudi Arabia has uncovered remains of a large early Islamic settlement. Paleolithic artefacts discovered in the building foundations of that settlement during the 2019 excavation showed that a Paleolithic site was buried partially by the settlement ruins. An archaeological exploration was carried out in the area around the site in March 2020 that documented three Paleolithic sites (Faid 1 – Faid 3). In February 2021, the archaeological survey was extended to the east and west of the settlement, resulting in the discovery of four additional Paleolithic sites (Faid 4 – Faid 7). The archaeological sites represented two main Paleolithic traditions: Acheulean, identified from the presence of bifaces, and Middle Palaeolithic, represented by production of prepared cores and points referable to the Levallois method. Faid 2 is an Acheulean site, where a systematic survey shows agglomeration of large cutting tools (LCTs) covering an area of 15 hectares. Handaxes and cleavers are the most conspicuous artefacts. Thus, the locations of these archaeological sites and lithic technocomplexes have direct relevance in assessing hominin dispersal routes through Arabia to the rest of Eurasia.